2018
DOI: 10.1002/ece3.3945
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of soil respiration to experimental litter manipulation in temperate woodland and tropical forest

Abstract: Global change is affecting primary productivity in forests worldwide, and this, in turn, will alter long‐term carbon (C) sequestration in wooded ecosystems. On one hand, increased primary productivity, for example, in response to elevated atmospheric carbon dioxide (CO 2), can result in greater inputs of organic matter to the soil, which could increase C sequestration belowground. On other hand, many of the interactions between plants and microorganisms that determine soil C dynamics are poorly characterized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
5
25
0
Order By: Relevance
“…Turnover and difference in variability in Bray-Curtis dissimilarity of each site for each group, with additional information on the amount of taxa during the 'high' and 'low' season, as well as the percentage of shared OTUs between the two time points. The lack of a correlation between interseasonal changes in community composition and edaphic parameters contradicts some of the earlier work on temporal changes in soil microbial communities (Bréchet et al 2018;Buscardo et al 2018;Lan et al 2018;Oberholster et al 2018;Ratcliffe, Bosman and Carnol 2018;Yang et al 2018;Zhang et al 2018). These studies found interseasonal changes in community composition or respiration, which were linked to temporal differences in precipitation, amount and quality of litter, and changes in the resident plant community.…”
Section: Temporal and Spatial Patterns Of Microbial Communitiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Turnover and difference in variability in Bray-Curtis dissimilarity of each site for each group, with additional information on the amount of taxa during the 'high' and 'low' season, as well as the percentage of shared OTUs between the two time points. The lack of a correlation between interseasonal changes in community composition and edaphic parameters contradicts some of the earlier work on temporal changes in soil microbial communities (Bréchet et al 2018;Buscardo et al 2018;Lan et al 2018;Oberholster et al 2018;Ratcliffe, Bosman and Carnol 2018;Yang et al 2018;Zhang et al 2018). These studies found interseasonal changes in community composition or respiration, which were linked to temporal differences in precipitation, amount and quality of litter, and changes in the resident plant community.…”
Section: Temporal and Spatial Patterns Of Microbial Communitiesmentioning
confidence: 78%
“…We discovered that difference in variability of communities, which can be interpreted as the difference in sample-to-sample variation between time points, has a very strong correlation between bacteria and all other groups, as well as between protists and fungi. As mentioned above, local differences in soil and biotic parameters exert a strong effect on microbial communities (Shi et al 2015;Dupont et al 2016;Tedersoo et al 2016;Bréchet et al 2018;Buscardo et al 2018). As communities become more variable on a local scale for one group, it is to be expected that other groups that are interacting with these microbes also become more variable.…”
Section: Bacteriamentioning
confidence: 99%
“…The increase in Rsoil with litter addition is likely due to the "priming effect," where an increase in labile C available to microorganisms enhances rates of microbial activity and degradation of SOM [21,22,25,29,53]. This could explain in part why Rsoil was positively related to SOM content ( Figure 5; Table 2).…”
Section: Effects Of Litter Pool Size On Co 2 Emission and Decompositionmentioning
confidence: 99%
“…The direct effects of litter production on Rsoil described here are consistent with results reported from other ecosystems, indicating that the effect of litter production on ecosystem C emission may be general across diverse forest types. For example, we compiled results from litter manipulation experiments reported in the literature [23,25,[27][28][29][49][50][51][52][53][54] and used linear regression to determine if there were consistent trends in the log response ratio of Rsoil [LN(Rsoil treatment/Rsoil control)] as a function of relative litter pool size ( Figure 6). Litter addition and/or removal resulted in surprisingly similar relative responses in Rsoil in spite of widely varying experimental methods (plot sizes, measurement intervals) and forest types ( Figure 6).…”
Section: Effects Of Litter Pool Size On Co 2 Emission and Decompositionmentioning
confidence: 99%
See 1 more Smart Citation